Effects of Lactobacillus plantarum-81-Fermented Feed on Growth and Intestinal Health of Muscovy Ducks - Zhaolong Li; Song Peng; Mengshi Zhao; Xiaodong Zhuang; Huini Wu; Tiecheng Sun; Fengqiang Lin (Fermentation)
Feed fermented by various strains of Lactobacillus plantarum (LP) produces distinct biologically active substances. This study systematically evaluates the growth performance, gut microbiota modulation, and immune response parameters in Muscovy ducks fed with LP81-fermented diets (LP81-FF) compared to conventional regimens. Our findings demonstrate that LP81-FF elicits dose-dependent improvements in Muscovy duck production parameters. Through a 70-day feeding trial, LP81-FF administration reduced feed intake by 3.1% and improved the average daily gain (ADG) and feed conversion ratio (FCR) by 9.18% and 6.65% (p < 0.05) compared to conventional feed. Systemic antioxidant capacity analysis revealed 25.99% elevation in total antioxidant capacity (T-AOC) (p < 0.05), accompanied by 14.37% and 30.79% increases in serum IgG and IgM levels, respectively. Immune organ indices showed dose-responsive enhancement, with the high-dose group (HD) achieving 47.27% and 28.92% increases in thymus and bursa of Fabricius indices (p < 0.05). Additionally, 16S rRNA sequencing revealed that LP81-FF optimized the intestinal microbial community structure of Muscovy ducks by promoting the abundance of Bacteroides, Butyricicoccus, and Ruminococcus (beneficial bacteria) (p < 0.05), while inhibiting the increase of Escherichia-Shigella and Rothia (harmful bacteria). It also promoted the secretion of beneficial metabolites such as Glutaric acid and 2,6-Diaminohexanoic acid in the intestine, inhibited the production of harmful substances dominated by Fexofenadine, and enhanced the strength of physical barrier-related factors such as intestinal mucosa villi and goblet cell count. These multi-omics insights establish that LP81-FF enhances growth performance through coordinated modulation of gut–liver axis homeostasis, mucosal immunity activation, and microbial-metabolic network optimization. Our results position LP81-FF as a sustainable alternative to antibiotic growth promoters in waterfowl production systems.